Kajian Kebutuhan Air dan Produktivitas Air Padi Sawah dengan Sistem Pemberian Air Secara SRI dan Konvensional Menggunakan Irigasi Pipa - Najla Anwar Fuadi; Muhammad Yanuar J. Purwanto; Suria Darma Tarigan (Jurnal Irigasi, 2016)
Limited water availability for agricultural land may cause decrease in rice production. The increase of crop production currently become a top priority in agricultural development. Productivity can be assessed through a subsystem of soil, water, and land patterns to use in certain periods. The applications of pipe irrigation with the combination of System of Rice Intensification (SRI) was capable to use water efficiently. Therefore, research concerning the calculation of water productivity of paddy rice which uses input pipe irrigation with conventional water supply system and SRI system is important to be conducted. The research steps were direct observation in the field, measurement of evapotranspiration, percolation, net field requirements and calculation of water productivity. The results showed that the production of rice was higher in water delivery system of SRI. Water productivity of paddy with SRI system also higher, where the water needs with a combination of pipe irrigation and water delivery systems in SRI were the best treatment. Water productivity in conventional rice fields was 0.82 kg/m3 and SRI 1.12 kg/m3. The combination of pipe irrigation and SRI systems showed high water productivity and efficient use of water.